PENGARUH KEAKTIFAN PENGURUS OSIS TERHADAP KARAKTER PERCAYA DIRI - Nur Aliyah, Siti; Kartakusumah, Berliana; Maryani, Novi (TADBIR MUWAHHID, 2019)
The activeness of the OSIS board is a useful to school activity and can develop the interests and talents of students and can influence the character of students, namely the character of self-confidence. The activity of students in the OSIS management is be expected to be able to instill and improve the character of students' self-confidence. The purpose of this research is to know to determine the effect of student council activeness on self-confidence characters. This type of research is to use the functional correlation method. The population and sample in the study were the members of OSIS board of SMAN 01 Ciawi for the period 2019-2020, totaling 42 people. Data collection techniques using interview, questionnaire, observation, and documentation techniques. The data analysis technique uses a simple linear regression formula. The results of the study based on the calculation of student council management activeness were relatively is good with an average mean score of 28,64 from the results of the overall number of respondents. The results of the study of the character of self-confidence are also relatively good with a mean score of 36,71 from the results of the total number of respondents as much as 40. The calculation of the coefficient of determination through the summary table model showed that as much as 90,1 % of characters are determined by the student council activists, while 90 , 1% is determined by other factors. Based on result, to find of statistic, the effect of the student council's activeness on the character of self-confidence in SMAN 01 Ciawi, Bogor Regency, which is positive but not significant, because the tcount of 1.831 is more than rtable 2.021. This the results of the regression to showed that Y = 23,420 + 0,466X. Based on the results of the research, it can be concluded that there was significant influence between the activeness of the Student Council administrators towards the character of self-confidence in SMAN 01 Ciawi, Bogor Regency, thus Ha was accepted and H0 was rejected.